2021
DOI: 10.1186/s12876-021-01739-z
|View full text |Cite
|
Sign up to set email alerts
|

Patient experiences with the role of physical activity in inflammatory bowel disease: results from a survey and interviews

Abstract: Background Physical activity may affect disease activity in patients with inflammatory bowel disease. We used a survey to investigate this association and performed interviews to get a better understanding of patient experiences, and therefore the nature of this association. Methods Patients with Crohn’s disease (CD, n = 176) and ulcerative colitis (UC, n = 162) completed the short Crohn’s Disease Activity (sCDAI) or Patient Simple Clinical Colitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…However, there was no difference between patients in remission and those with active disease. Comparable results were found in a similar study, with only 60% of patients adhering to the WHO recommendations [9]. Finally, in a case-control study, Qalqili et al [10] evaluated the difference regarding some lifestyle parameters, including physical activity, among 185 newly-diagnosed IBD patients (100 UC and 85 CD) and 150 healthy controls.…”
Section: Level Of Physical Activity In Inflammatory Bowel Disease Pat...mentioning
confidence: 92%
See 1 more Smart Citation
“…However, there was no difference between patients in remission and those with active disease. Comparable results were found in a similar study, with only 60% of patients adhering to the WHO recommendations [9]. Finally, in a case-control study, Qalqili et al [10] evaluated the difference regarding some lifestyle parameters, including physical activity, among 185 newly-diagnosed IBD patients (100 UC and 85 CD) and 150 healthy controls.…”
Section: Level Of Physical Activity In Inflammatory Bowel Disease Pat...mentioning
confidence: 92%
“…Olive et al [28] showed that anxiety and depression were a limitation to physical activity in adult patients with chronic disease, including IBD. Other frequent obstacles to physical activity reported by patients with IBD included fatigue, pain and faecal urgency [9]. Stoma and repeated surgical procedures also appear to limit physical activity.…”
Section: Challenges Related To Physical Activity In Inflammatory Bowe...mentioning
confidence: 99%
“…However, as there was no clear distinction in how they responded to the questions in the interviews, they were all analysed as one group. Other studies using semi-structured interviews indicated to have achieved data adequacy with less than 20 participants [23][24][25][26]. Therefore, it was intended to recruit 20 participants (10 in each group) and then recruit additional participants until data adequacy was achieved.…”
Section: Methodsmentioning
confidence: 99%
“…Using multiple linear regressions and survey data, Lamers et al . [ 118 ] reported that CD patients with higher physical activity levels had lower reported disease activity. It should only be cautiously assumed that these patients had higher physical activity levels due to more higher-intensity activities.…”
Section: Equivocal Effects Of High-intensity Exercise and Relevant Co...mentioning
confidence: 99%
“…A multiple linear regression analysis by Lamers et al . [ 118 ] showed that when CD disease activity was increased, physical activity scores decreased ( P = 0.035). Brevinge et al .…”
Section: Equivocal Effects Of High-intensity Exercise and Relevant Co...mentioning
confidence: 99%